Counseling and Education on Mother's Knowledge and Attitude in Providing Exclusive Breastfeeding with Video Media - Husna Mujahidah; Melly Kristanti; Marlina Dewiastuti; Aulia Chairani (Sarana Ilmu Indonesia (Salnesia), 2025)
Knowledge and attitudes were expected to improve through health promotion and education by using the advantages of video media, thereby increasing the coverage of exclusive breastfeeding. This study aimed to evaluate the effectiveness of video-based education in improving maternal knowledge and attitudes. Mampang, one of the subdistricts in Depok City, was selected as the research location due to its higher rates of infant mortality and stunting compared to most other areas in Depok City. The study sample consisted of 32 breastfeeding mothers selected using purposive sampling. This study applied the McNemar test with a quantitative approach and a pre-experimental one-group pretest–posttest design. The statistical analysis showed a significant increase in maternal knowledge, rising from 59,4% to 93,8% after participating in video-based counseling and education (p-value = 0,003; p-value < 0,05). However, the results indicated no significant effect of video-based counseling and education on maternal attitudes, which changed from 56,2% to 75,0% (p-value = 0,070; p-value > 0,05). Video-based education was found to be more effective and informative, particularly for young adult mothers. Therefore, health promotion workers at primary healthcare centers could use this method as an alternative educational strategy alongside leaflets or posters.